치매 환자의 행동심리 증상완화를 위한 가상현실 프로그램의 효과 - 박선민; 최승이; 김정희; Park, Seon-Min; Choi, Seung-Yi; Kim, Jung-Hee (Journal of Korean Academy of Nursing, 2022)
Purpose: This study examined the impact of a virtual reality intervention program based on psychological needs on behavioral and psychological symptoms, apathy, and quality of life (QOL) in patients with dementia or mild cognitive impairment living in nursing facilities. Methods: This study is nonequivalent control group pretest-posttest design of quasi-experimental study. The study collected data from November 18, 2020 to July 24, 2021 from patients with dementia or mild cognitive impairment (30 in the experimental group and 30 in the control group) at three nursing facilities in G city using self-reporting and caregiver-informant reporting methods. The analysis employed the chi-square test, Fisher's exact test, paired t-test, independent t-test, Wilcoxon signed rank test, Mann-Whitney U, repeated measures ANOVA, GEE, using SPSS/WIN 27.0. Results: The severity of behavioral and psychological symptoms (Wald 2 = 2.68, p = .102) and the care burden of caregivers (Wald 2 = 1.72, p = .190) were not significant and was no significant time and group interaction effect (Wald 2 = 0.63, p = .426, Wald 2 = 0.52, p =. 471). The difference in apathy and QOL score were statistically significant for the group-time interaction (F = 43.65, p < .001; F = 4.35, p = .041). Conclusion: The virtual reality intervention program of this study shows a positive effect on the apathy reduction and QOL of patients with dementia or mild cognitive impairment residing in nursing facilities.